Growth Test of Pakchoy (Brassica rapa L) Against Abiotic Stress from the Heavy Metal Pb: Uji Pertumbuhan Tanaman Pakcoy (Brassica rapa L) Terhadap Cekaman Abiotik Logam Berat Pb - Widya, Surya Ari; Helios, Sergio; Inti, Ristani Widya; Larissa, Damasa Ines (Journal of Applied Plant Technology, 2023)
The pakchoy plant also faces various challenges in its growth environment, including exposure to abiotic stressors. Heavy metals, such as lead (Pb), are environmental contaminants that can have significant negative impacts on plants. Therefore, this research aims to investigate the resilience of pakchoy plants (Brassica rapa L.) to concentrations of abiotic stress from the heavy metal Pb. This is achieved through a series of experiments to understand the effects of exposure to the heavy metal Pb on growth and to analyze the accumulation of heavy metals in pakchoy plants. Pakchoy plants (Brassica rapa L.) can grow under conditions of heavy metal Pb stress; however, as the concentration of Pb increases, the growth of the plants becomes progressively slower. This is evidenced by a reduction in height, leaf number, plant biomass, and the accumulation of heavy metal Pb in the plant tissues. Consequently, these plants are categorized as phytoremediators due to their ability to accumulate heavy metal Pb.